Calcium and transcription-coupling - Lounsbury, Karen (Henry Stewart Talks, 2007)
Calcium sources, Calcium-regulated transcription factors: Calcium/cAMP response element binding protein (CREB), nuclear factor of activated T-cells (NFAT) and serum response factor (SRF), Calcium signaling cascades, Calcium and cell differentiation, Calcium and disease
Updated at 2013/09/22